2016
DOI: 10.1039/c6fd00002a
|View full text |Cite
|
Sign up to set email alerts
|

Advances in electroanalysis, sensing and monitoring in molten salts

Abstract: Microelectrodes have a number of advantages over macroelectrodes for quantitative electroanalysis and monitoring, including reduced iR drop, a high signal-to-noise ratio and reduced sensitivity to convection. Their use in molten salts has been generally precluded by the combined materials challenges of stresses associated with thermal cycling and physical and corrosive chemical degradation at the relatively high temperatures involved. We have shown that microfabrication, employing high precision photolithograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In the manufacture of microelectrode systems capable of sensing multiple analytes on a single device, photolithographic microfabrication techniques from the silicon integrated circuit industry are particularly attractive due to the ability to fabricate precise and reproducible structures of known shape and dimension [ 14 ]. Recent studies have demonstrated the successful fabrication of devices using such methods and the subsequent electrochemical measurements on electrodes of controlled shape and dimensions [ 15 , 16 , 17 ]. In addition, recent work has systematically investigated the combinations of device layers and materials to achieve optimal electrochemical responses and durability [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the manufacture of microelectrode systems capable of sensing multiple analytes on a single device, photolithographic microfabrication techniques from the silicon integrated circuit industry are particularly attractive due to the ability to fabricate precise and reproducible structures of known shape and dimension [ 14 ]. Recent studies have demonstrated the successful fabrication of devices using such methods and the subsequent electrochemical measurements on electrodes of controlled shape and dimensions [ 15 , 16 , 17 ]. In addition, recent work has systematically investigated the combinations of device layers and materials to achieve optimal electrochemical responses and durability [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…They offer a number of advantages over macroelectrodes for electrochemical sensing 5 in chemical 3 , industrial 6,7 and medical applications 8 . These advantages make microelectrodes and arrays of microelectrodes an attractive technology for sensitive and specific detection of biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…This estimate identified that 75% of the current leakages were in a range of 10 A to 1 nA. These current levels are in the range of the currents recorded in electrochemical measurements with microelectrodes [7]- [9]. This means identifying small leakage currents when using microelectrodes is difficult in the majority of cases.…”
Section: Elementmentioning
confidence: 97%
“…These microelectrodes had a yield of only 45.8% (n = 84) when operated in the LKE. Functioning microelectrodes demonstrated quantifiable steady-state currents of around 50 -500 nA depending on the microelectrode size [7], [9]. The majority of failed IMLs exhibited high currents of the order of 1 -10 A and no steady-state current.…”
Section: A Yieldmentioning
confidence: 99%